Cerebrospinal fluid levels of neopterin are elevated in delirium after hip fracture. Issue 1 (December 2016) - Hall, Roanna; Watne, Leiv; Idland, Ane-Victoria; Raeder, Johan; Frihagen, Frede; MacLullich, Alasdair; Staff, Anne; Wyller, Torgeir; Fekkes, Durk
Abstract Background The inflammatory cell product neopterin is elevated in serum before and during delirium. This suggests a role for disordered cell-mediated immunity or oxidative stress. Cerebrospinal fluid (CSF) neopterin levels reflect brain neopterin levels more closely than serum levels. Here we hypothesized that CSF neopterin levels would be higher in delirium. Methods In this prospective cohort study, 139 elderly patients with acute hip fracture were recruited in Oslo and Edinburgh. Delirium was diagnosed with the confusion assessment method performed daily pre-operatively and on the first 5 days post-operatively. Paired CSF and blood samples were collected at the onset of spinal anaesthesia. Neopterin levels were measured using high-performance liquid chromatography. Results Sixty-four (46 %) of 139 hip fracture patients developed delirium perioperatively. CSF neopterin levels were higher in delirium compared to controls (median 29.6 vs 24.7 nmol/mL, p = 0.003), with highest levels in patients who developed delirium post-operatively. Serum neopterin levels were also higher in delirium (median 37.0 vs 27.1 nmol/mL, p = 0.003). CSF neopterin remained significantly associated with delirium after controlling for relevant risk factors. Higher neopterin levels were associated with poorer outcomes (death or new institutionalization) 1 year after surgery (p = 0.02 for CSF andp = 0.03 for serum). Conclusions This study is the first to examine neopterin in CSF from patients with delirium. Our findings suggest potential roles for activation of cell-mediated immune responses or oxidative stress in the delirium process. High levels of serum or CSF neopterin in hip fracture patients may also be useful in predicting poor outcomes.